Analysing socioeconomic diversity and scaling effects on residential electricity load profiles in the context of low carbon technology uptake. (October 2016) - McKenna, R.; Hofmann, L.; Merkel, E.; Fichtner, W.; Strachan, N.
Abstract: Adequately accounting for interactions between Low Carbon Technologies (LCTs) at the building level and the overarching energy system means capturing the granularity associated with decentralised heat and power supply in residential buildings. The approach presented here adds novelty in terms of a realistic socioeconomic differentiation by employing dwelling/household archetypes (DHAs) and neighbourhood clusters at the Output Area (OA) level. These archetypes are combined with a mixed integer linear program (MILP) to generate optimum (minimum cost) technology configurations and operation schedules. Even in the baseline case, without any LCT penetration, a substantial deviation from the standard load profile (SLP) is encountered, suggesting that for some neighbourhoods this profile is not appropriate. With the application of LCTs, including heat pumps, micro-CHP and photovoltaic (PV), this effect is much stronger, including more negative residual load, more variability, and higher ramps with increased LCT penetration, and crucially different between neighbourhood clusters. The main policy implication of the study is the importance of understanding electrical load profiles at the neighbourhood level, because of the consequences they have for investment in the overarching energy system, including transmission and distribution infrastructure, and centralised generation plant. Further work should focus on attaining a superior socioeconomic differentiation between households. Highlights: Low carbon technologies (LCTs) for heat/electricity in residential buildings. Socioeconomic effects and interactions with overarching energy system. Building thermal/electrical model combined with optimisation. Significant differences between neighbourhood load profiles. Policy implications: support for LCTs and investment in infrastructure.